KARAKTERISTIK MORFOLOGI BIBIT CENDANA (Santalum album L.,) YANG DITANAM PADA CEKAMAN AIR TANAH ALVISOL DAN VERTISOL - Sarah Kahi Timba; Rahel Suhardjana (Politeknik Pertanian Negeri Kupang, 2022)
Santalum album L. is endemic plant and has economic valeu for East Nusa Tenggara. The Populatian is decreasing. And it must be done by taking the best seeds from the field. The research was conducted in Kupang Regency, for 6 months. The technigue used in this study was a factorial randomized block design with 3 replications. The first factor is groundwater absorption (CO); (C1); (C3); (C3); (C4) factor of both Alfisol and Vertisol soils. The results showed that two days of absorption (C2) on Vertisol soil and one day of absorption (C1) on Alfisol produced the best sandalwood in terms of hautorium number, plant height, stem diameter, leaf weight, compared to other nipples, it is recommended to use two days of absorption C2) on Vertisol soil and one day of absorption (C1) on Alfisol because the seeds are in polybag.Keywords: sandalwood, absorption, alfisol and vertisol soil